2016
DOI: 10.3389/fphar.2016.00331
|View full text |Cite
|
Sign up to set email alerts
|

Axitinib after Sunitinib in Metastatic Renal Cancer: Preliminary Results from Italian “Real-World” SAX Study

Abstract: Axitinib is an oral angiogenesis inhibitor, currently approved for treatment of metastatic renal cell carcinoma (mRCC) after failure of prior treatment with Sunitinib or cytokine. The present study is an Italian Multi-Institutional Retrospective Analysis that evaluated the outcomes of Axitinib, in second-line treatment of mRCC. The medical records of 62 patients treated with Axitinib, were retrospectively reviewed. The Progression Free Survival (PFS), the Overall Survival (OS), the Objective Response Rate (ORR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
1
8
1
Order By: Relevance
“…Previous real-world studies comparing the effectiveness of second-line targeted therapies for mRCC used different designs and reported heterogeneous results, with no convincing evidence of a difference in effectiveness between mTORi and VEGF TKI in the second-line setting [37]. Our results build on the existing real-world evidence which supports the benefits of second-line axitinib treatment over everolimus after prior anti-VEGF therapy [38][39][40] in patients showing longer DFT on first-line sunitinib treatment.…”
Section: Discussionsupporting
confidence: 52%
“…Previous real-world studies comparing the effectiveness of second-line targeted therapies for mRCC used different designs and reported heterogeneous results, with no convincing evidence of a difference in effectiveness between mTORi and VEGF TKI in the second-line setting [37]. Our results build on the existing real-world evidence which supports the benefits of second-line axitinib treatment over everolimus after prior anti-VEGF therapy [38][39][40] in patients showing longer DFT on first-line sunitinib treatment.…”
Section: Discussionsupporting
confidence: 52%
“…To date there are no head-to-head studies or randomized clinical trials, that provide conclusive information about the best second-line. Several ‘real world’ studies confirmed the efficacy and safety of Axitinb in a not selected population [1224].…”
Section: Introductionmentioning
confidence: 98%
“…Patients enrolled in the AXIS trial who reported a diastolic blood pressure ≥90 mmHg within the first 8 or 12 weeks of randomization had a longer survival independently on the treatment arm: 20.7 months (95% CI 18.4-24.6) vs. 12.9 months (95% CI 10.1-20.4) in the axitinib group (p = 0.01), and 20.2 months (95% CI 17.1-32.0) vs. 14.8 months (95% CI 12.0-17.7) in the sorafenib group (p = 0.002) (77). These findings could not be confirmed by the Italian SAX study on real-world use of axitinib (120). A recent retrospective study showed that grade 3 hypertension affected positively OS in patients treated with pazopanib in real-world settings (HR=0.22, 95% CI 0.05-0.8, p = 0.03) (121).…”
Section: Hypertensionmentioning
confidence: 86%